Loss Minimization in Optimal Reactive Power Planning (ORPP) Based on Whale Optimization Algorithm - Hakimin Nasru, Muhammad; Musirin, Ismail; Khairuzzaman Mohamad Zamani, Mohamad; Rafidah Abdul Rahim, Siti; Hatta Hussain, Muhamad; Suyono, Hadi (International Journal of Engineering and Technology, 2018)
The key of RPP is the optimal allocation of reactive power considering location and size. This paper presents the loss minimization in optimal reactive power planning (ORPP) based on Whale Optimization Algorithm (WOA). The objective is to minimize transmission loss by considering several load conditions at bus 3, bus 15 and bus 21. Reactive Power Scheduling (RPS) and Transformer Tap Changer Setting (TTCS) were set as the control variables. Validation was conducted on the IEEE 30 Bus RTS. Results from the study indicate that the proposed WOA can minimize transmission loss better than Evolutionary Programming (EP).Â